Is local plant extinction a product of mutualism breakdown? A case study of the Namaqualand spring flora - Smuts, Rowena (Department of Biological Sciences, 2021)
A mutualism-centred risk assessment model, proposed by Bond (1993), was used to predict which plant species are vulnerable to extinction in the absence of insect pollinators. The predictions of this model were then compared with actual plant species compositions between adjacent disturbed and undisturbed sites in a Namaqualand flowering community. It was found that autogamous annuals were at the lowest risk of extinction and were consequently abundant in disturbed lands. Geophytes were completely eliminated by ploughing, however, the cause of their local extinction is not necessarily due to mutualism breakdown and may be explained by a lack of seed banks. The model was shown to be useful for predicting distribution patterns for annuals. However, further studies of seed banks, germination cues and colonisation success are necessary to make predictions for the geophytic species. The study illuminated the fact that both plant and associated insect species diversity decline rapidly in disturbed areas and that the elimination of insects, by ploughing, may lead to extensive loss of plant species.